Piston secondary motion measurement by laser displacement sensors - Dlugoš, Jozef; Novotný, Pavel (JVE Intenational, 2018)
Measurement of the piston group behavior is still a challenge. Achieved accuracy and complexity go hand in hand with the financial requirements. This paper presents an unconventional measurement of the piston secondary motion using laser displacement sensors. Two sensors help capture the piston tilt angle, while the third sensor is used for the piston lateral motion measurement. These sensors are aimed at the piston crown. The passage between the laser source and the target spot has to be transparent. Therefore, side-valve internal combustion engine is employed. It enables the cylinder head to be made of the transparent material such as cast plexiglass. In the initial stage, the experimental engine is motored during the measurement. As for the measurement of the piston tilt angle, the results are within the physical limits. However, the same does not apply for the piston lateral results, where the measured values are too high, so the piston would penetrate the liner.

Measurement of the piston group behavior is still a challenge. Achieved accuracy and complexity go hand in hand with the financial requirements. This paper presents an unconventional measurement of the piston secondary motion using laser displacement sensors. Two sensors help capture the piston tilt angle, while the third sensor is used for the piston lateral motion measurement. These sensors are aimed at the piston crown. The passage between the laser source and the target spot has to be transparent. Therefore, side-valve internal combustion engine is employed. It enables the cylinder head to be made of the transparent material such as cast plexiglass. In the initial stage, the experimental engine is motored during the measurement. As for the measurement of the piston tilt angle, the results are within the physical limits. However, the same does not apply for the piston lateral results, where the measured values are too high, so the piston would penetrate the liner.
Piston secondary motion measurement by laser displacement sensors
Keywords: piston secondary motion; piston group; dynamics; internal combustion engines; laser displacement sensor; piston secondary motion; piston group; dynamics; internal combustion engines; laser displacement sensor